The guardian - Lewis, Beverly, 1949- (Lewis, Beverly, 1949- Home to Hickory Hollow., 2013)
After schoolteacher Jodi Winfield finds a little girl on the side of the road, she delves into the isolated community of the Lancaster Old Order Amish to find a